Effects of Growing Incomes on Classified Income Distributions, the Derived Lorenz Curves, and Gini Indices - Petersen, Hans-Georg (Econometrica, 1979)
The purpose of this paper is to indicate the problems connected with the intertemporal comparability of Lorenz curves and Gini indices estimated by standard numerical approaches in the case of the classified empirical income distribution and a growth of individual income at a fixed rate. Collector effects of the higher intervals lead to shifts of the Lorenz curve to the right or to the left; accordingly the Gini index may rise or fall. This class phenomenon occurs although actually nothing has changed in distribution.